Use of 4-Nitroquinoline 1-Oxide (4NQO) in Dysplastic and Malignant Induction: In Vitro and In Vivo Studies - Meneses, Daniela Oliveira [UNESP]; Souza, Brunna da Silva Nobrega [UNESP]; Dutra, Mateus José [UNESP]; Malta, Isabella Souza [UNESP]; Silva, Bruna Oliveira [UNESP]; Cançado, Isis Moraes [UNESP]; Conceição, Nathan Stevan Cezar [UNESP]; Lança, Maria Leticia de Almeida [UNESP]; Vasconcellos, Luana Marotta Reis de [UNESP]; Kaminagakura, Estela [UNESP] (MDPI, 2025)
Objectives: Tobacco has been associated with the development of oral leukoplakia (OL) and oral squamous cell carcinoma (OSCC). This study aimed to evaluate the in vitro and in vivo changes caused by carcinogen 4-nitroquinoline 1-oxide (4NQO), simulating smoking conditions. Materials and Methods: In the in vitro study, normal keratinocytes were exposed to 1.3 µM and 2.6 µM concentrations of 4NQO to induce dysplastic transformation (H-DISP) and malignant transformation (H-SCC), respectively. The cells were collected and subjected to hematoxylin and eosin (H&E) staining and immunocytochemistry with Ki-67. For the in vivo study, female C57BL/6J mice were divided into a pure control (PC) group and experimental groups exposed to 50 µg/mL (NQ) and 100 µg/mL (CM) of 4NQO in autoclaved drinking water. Each group was euthanized after 8, 12, 16, and 20 weeks of exposure. The tongues were collected, processed, stained with H&E, and analyzed using conventional light microscopy. Results: In vitro, significant morphological changes were observed in the H-DISP and H-SCC groups, with a cell proliferation index exceeding 30% in the H-DISP group. In vivo, the CM group showed greater progression to severe dysplasia/carcinoma within a shorter treatment period compared to the NQ group. Conclusions: We established critical doses and exposure durations for 4NQO, both in vitro and in vivo, to induce cellular changes and the formation of OL and OSCC, providing a standardized model for studies related to oral carcinogenesis.